Potential for Drought Tolerance in Greengram - Anitha A R (Department of Plant Breeding, College of Agriculture, 1989)
A research programme was carried out at the Department of Plant Breeding, College of Agriculture, Vellayani, during October to December, 1988 with an objective of evaluating the potential for drought tolerance in greengram through esimation of genetic variability, correlation of yield with component characters and the direct and indirect effects of different components on yield. Twenty varieties of greengram were evaluated under open conditions without any irrigation adopting a randomized block design replicated thrice. Data on twenty characters were recorded and subjected to analysis of varience and covariance. The genotypic and phenotypic coefficient of variation, heritability in the broad sense, genetic advance and genotypic and phenotypic correlations were estimated. Path analysis was conducted with yield per plant as the effect and seven component characters as the cause. Analysis of variance revealed significant difference among the varieties for plant height, number of leaves per plant, pod length, number of seeds per pod, hundred seed weight, seed size, yield per plot, haulm yield, stomatal distribution, leaf area index, root length, root spread, root/shoot ratio, days to first flowering, days to maturity of first pod, days to final harvest and grain filling period. Analysis of variance for number of pods per plant, yield per plant and proline content revealed no significant difference among varieties. Maximum heritability was recorded for grain filling period. The yield components, pod length, number of seeds per pod, hundred seed weight and seed size recorded moderate to high heritability and genetic gain. Grain yield per plant recorded significant positive genotypic correlations with number of pods per plant, hundred seed weight, grain filling period and proline content. Significant negative genotypic correlations were recorded with plant height, pod length, number of seeds per pod, leaf area index and days to first flowering. Path analysis revealed that number of pods per plant had the maximum direct distribution for grain yield followed by plant height, days to first flowering and pod length. Root/shoot ratio and seed size exhibited negative indirect effect on yield. Seed size exerted positive indirect effect through number of pods per plant. The study thus reveals that in greengram early varieties of medium height and leaf area index having longer grain filling period, more number of pods and a moderately high seed size and weight are suitable for cultivation under moisture stress conditions.